2017
DOI: 10.5455/msm.2017.29.97-100
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Depression and its Correlation with Quality of Life of Patients with Oral Cavity Cancer

Abstract: Introduction:the effects of malignant tumors of oral cavity may be reflected through mental, physical, social and emotional well-being and quality of life of patients. Those suffering from malignancies show a large degree of psychological problems (fear, anxiety, depression, panic disorders, phobias) both at the time of diagnosis and during the treatment.Aim:to determine a level of depression in patients with oral cavity cancer and to link quality of life and level of depression of patients with oral cavity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A number of studies have reported that chronic stress interferes with immune, endocrine and neural system functions. A number of epidemiological and clinical studies have reported that chronic stress plays an essential role in cancer occurrence, development and mortality, and reducing stress may prolong survival and decrease recurrence after therapy (14)(15)(16)(17). It has been demonstrated that chronic stress can activate the HPA axis and the SNS, leading to a release of catecholamines (NE, epinephrine and dopamine), glucocorticoids and other hormones.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that chronic stress interferes with immune, endocrine and neural system functions. A number of epidemiological and clinical studies have reported that chronic stress plays an essential role in cancer occurrence, development and mortality, and reducing stress may prolong survival and decrease recurrence after therapy (14)(15)(16)(17). It has been demonstrated that chronic stress can activate the HPA axis and the SNS, leading to a release of catecholamines (NE, epinephrine and dopamine), glucocorticoids and other hormones.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Similar attention to poor oral health was also documented among cancer patients. 3 , 4 The psychological distress and poor oral health were negatively related with time, because of the diagnoses of cancer, 3 , 5 treatment, 4 , 6 and poor prognosis in cancer patients. 7 , 8 In Saudi Arabia, due to a wide array of national screening programs and diagnosis of new cancer cases at an early stage, 9 the survival rate among cancer patients continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenes and tumour suppressor genes such as CCND1 , EGFR , RAS , VEGF , p53 , CDKN2A , STAT3 , and Rb have been implicated in oral cancer [ 11 , 12 , 13 ]. Oral cancer is preventable and curable in early stages, but the majority of cases of oral squamous cell carcinomas (OSCC) are not diagnosed until advanced stages, a point at which therapy is less effective and the prognosis is worse [ 14 , 15 ]. Tissue biopsy is the gold standard in the diagnosis of oral cancer, but it is invasive, costly, and time-consuming, and it is potentially harmful.…”
Section: Introductionmentioning
confidence: 99%